A nineteenth-century American Reader - Inge, M. Thomas, Editor (United States Information Agency, 1988)
Westward expansion and the American Mission -- The temperament of the Frontiersman -- The influence of the Frontier -- Patterns of Trought -- Tradition and Innovation in Literature -- Social progress -- Divergent civilizations -- Slavery and disunion -- Industrial triumph and Confrontation of Reality